Analyzing the Measures of Credit Risk on Financial Corporation and It’s Impact on Profitability - Hai Lam (International Journal of Research in Vocational Studies (IJRVOCAS), 2023)
Non-Banking Financial Corporations are playing a major role in the financial market with respect to providing loan facilities to the business. It is an integral the financial system of any country. It leads to improvise the employment opportunities and economic development. The NBFCs are becomes an important stimulant of credit creation and credit control tool of central banks of the respective countries. The dispersal of loans and advances provided to individuals and the companies are contained the credit risk for the NBFCs. Gumrarathi (2010) study reveals that most of the non-banking financial corporation’s business operations are holding a high credit risk in lending. It shows that most of the lending transacted with small and medium level organizations, which is having a probability of high-risk class. The NBFCs are already encountering various issues such as high fund cost, poor industrial development, and huge competition among the NBFCs and also with commercial banks. The non-performing assets are another kind of big issue in reducing the profitability. In this juncture, the management of this credit risk is one of the prominent challenges of the Non-Banking Financial Corporations. Because the credit risk is the direct risk and their whole business life survival is based on the money which is invested on loans. The credit risk measures are coming into existence to mitigate the losses arise through the non-performing assets (NPA). The present study aims to analyze the various strategies adopted by the selected NBFCs. It is attempted to find out the credit risk measurement and controls systems of NBFCs. The study also analyzes the relationship between the credit risk measures of corporations and its profitability. Present study is adopted the descriptive research method to carry out the study. It is purely based on the secondary data sources such as financial statements, published data of NBFCs and data published in journals. The collected data is analyzed by applying appropriate econometric tools such as stationarity, cointegration, and granger causality to find the relationship among the variables. Based on the data analysis, the results are interpreted and conclusions are made. The present study provides the strong evidences of strong relationship among the credit risk management, control of non-performing assets and the profitability of the NBFCs.